Apatite geochemistry of granites from the Xiaolonghe Tin deposit, Western Yunnan: Implications for petrogenesis and mineralization - Kun Ge; Xiang Sun; Yong Fu; Yaqi Ye; Yingjie Wang; Xianyi Huang; Xiaobo Si; Mingjun Zheng (Journal of Geochemical Exploration, 2026)

Decoupling of evapotranspiration from atmospheric demand: mechanistic insights into the local evaporation paradox in arid shrublands via physical and physiological resistance thresholds - Yuquan Qiang; Mingjun Zhang; Yu Zhang; Shengjie Wang; Xianying Xu; Jinchun Zhang; Guiquan Fu; Zhilan Wang; Meilin Sun; Peng Zhao; Shiquan Liu (Journal of Hydrology, 2026)

Synergic anticancer effects of morin hydrate and sorafenib delivered via polymeric iron oxide nanoparticles for the treatment of triple-negative breast cancer - Mingjun Li; Chaohui Wang; Zhenhua Sun (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Projection of surface air temperature and precipitation in High Mountain Asia and its major upstream river basins through multi-model ensemble from CMIP6 - Shu Wang; Meiping Sun; Xiaojun Yao; Mingjun Zhang; Ruiyi Fan; Weisheng Wang (Journal of Mountain Science, 2026)

Mobile self-assembled membranes: A novel strategy for boosting light hydrocarbon separation efficiency - Yanan Jia; Zixuan Huang; Minglong Wang; Zhi Li; Hongyi Yu; Jun Xu; Bei Liu; Mingjun Deng; Jingming Li; Kun Li; Mingke Yang; Ruihang Zhang; et al. (Chemical Engineering Journal, 2026)

Integrative multi-omics identifies CYP1B1 as a candidate molecular link between toxicant exposure and ferroptosis-related epithelial stress in COPD - Lingfeng Liu; Mingjun Jiang; Muzi Lei; Kun Du; Xiangyang Ye; Dafei Wei; Xiaowu Tan; Zhuang Mi; Yao Tang; Ruiting Sun; Sha Liu (Inflammation Research, 2026)

A bimodal phenomenon in lake evolution since the last deglaciation from Qinghai-Tibet Plateau: Multiple hypothesis verification and a new mechanism - Zhansen Zhang; Yu Li; MingJun Gao; Hao Shang; Shiyu Liu; Jiarui Zhao; Tingting Xi; Wanchen Sun (Global and Planetary Change, 2026)

Mechanistic Insight into Formation and Release Enhancement of Sulindac-Amino Acid Small-Molecule Hydrogels - Jiaxin Chen; Huizhen Sun; Wuheng Yue; Zhimin Yue; Baimin Niu; Mingjun Li; Xinru Lu; Jue Wang; Xiaoqian Liu; Jiawei Han (Pharmaceutical Research, 2026)

Intelligent trajectory tracking control for autonomous sailboats based on event-triggered NMPC and adaptive reference trajectory - Hongqiang Sang; Mingjun Jia; Xiujun Sun; Fen Liu; Yanhong Wang (Ocean Engineering, 2026)

Asymmetric Fe–Co dual-atom sites enable electron-transfer-dominated peracetic acid oxidation - Mingjun Xie; Yuying Han; Congting Sun; Shuyan Zang (Journal of Environmental Sciences, 2026)

Carbon vacancies modulated confined Fe single-atoms on loofah-derived biochar for Fenton-like process via non-radical PAA activation - Mingjun Xie; Yuying Han; Dandan Wang; Congting Sun; Shuyan Zang (Chemical Engineering Journal, 2026)

Luteolin exhibits broad-spectrum antiviral activity against swine enteric coronaviruses by targeting 3CLpro - Xiaoxu Xing; Jiongze Cheng; Huinan Li; Ming Liu; Minghui Gu; Jiawei Xiao; Hansong Li; Lan Bi; Feiyu Zhao; Haixin Liu; Donghua Guo; Mingjun Su; et al. (Veterinary Microbiology, 2026)

Hydrate stability assessment in marine environments: Implications for CO2 sequestration site optimization - Lei Zhang; Wei Song; Fei Huang; Bingbing Chen; Huiru Sun; Mingjun Yang (Journal of Environmental Chemical Engineering, 2026)

SERPINB1 promotes porcine deltacoronavirus replication by targeting the viral accessory protein NS7a - Junfang Yan; Xinru Liu; Huixin Zhu; Liang Li; Hongye Pan; Renjie Bao; Qiutian Li; Jing Sun; Houhui Song; Mingjun Su (Veterinary Microbiology, 2026)

A fast powerful X-ray transient from possible tidal disruption of a white dwarf - Dongyue Li; Wenda Zhang; Jun Yang; Jin-Hong Chen; Weimin Yuan; Huaqing Cheng; Fan Xu; Xinwen Shu; Rong-Feng Shen; Ning Jiang; Jiazheng Zhu; Chang Zhou; et al. (Science Bulletin, 2026)

Preparation, structure and application in energy storage and conversion of metal organic frameworks and covalent organic frameworks composite materials - Huizhen Sun; Mingjun Xiao; Yanjie Qi; Xihang Dai; Botao Wang; Yue Jiang (Journal of Environmental Chemical Engineering, 2026)

CO2 injection strategies to enhance the sequestration capacity in oceanic reservoir for hydrate-based carbon storage - Xinru Wang; Jing Chen; Huiru Sun; Bingbing Chen; Xin Lv; Weixin Pang; Yongchen Song; Mingjun Yang (Fuel, 2026)

Salicylic acid as a pathway inducer for improved bioremediation of oil-polluted saline-alkali soils by chemotactic S. Stutzeri M3 - Lin Li; Xiaoying Yu; Mingjun Wang; Huaji Sun; Jingyi Zhu; Xuehan Wang; Shuiquan Chen; Shugang Hu (Bioresource Technology, 2026)

Gene editing and association analysis of circadian clock gene TaPRR59 highlights its importance in yield-related traits in wheat - Jinrong Li; Meijie Zhu; Guimei Hu; Xiaoyue Chen; Huixian Xue; Yuanxun Zhang; Yifan Wang; Ziqi Li; Dengke Xu; Mingjun Zhai; Guangsheng Zhou; Chenxiao Cui; et al. (Theoretical and Applied Genetics, 2026)

Magmatic controls and chronology of tin mineralization in the Mengsong Deposit, Southern Lincang Batholith, SW China - Jiale Wang; Xiaobo Si; Mingjun Zheng; Huanchao Xu; Xiang Sun (Journal of Geochemical Exploration, 2026)

Colloidal electrolyte–mediated dispersion and transport mechanism: Enhancing stability and efficiency of MnO2-based slurry flow battery - Mingjun Nan; Jiaying Yan; Qizhen Cui; Wanyao Sun; Shujie Gao; Xinyu Guo; Wendi Jin; Xiangkun Ma (Chemical Engineering Journal, 2026)

Development of a core streptavidin-bridging amplified ELISA based on p54 epitope for high-sensitivity detection of african swine fever virus antibodies - Jing Sun; Yingshan Zhou; Xingbo Liu; Xiaoxu Du; Jiongze Cheng; Huihua Zheng; Shuonan Pan; Junfang Yan; Xingdong Zhou; Xiaodu Wang; Zixiang Zhu; Dongbo Sun; et al. (The Veterinary Journal, 2025)

Microwave-assisted functionalization of waste PET plastic with bio-oil: Enhancing compatibility with asphalt through molecular simulation and experimental analysis - Mingjun Hu; Kai Zhu; Qihan Zhang; Guoqiang Sun; Arpatjiang Abudurahman (Fuel, 2025)

Identification of antioxidant peptides from a bioactive peptide database PWDB of walnut family protein hydrolysates - Tianle Zhang; Dingwei Zheng; Siyuan Qian; Mingjun Du; Caiyun Li; Zhichao Sun; Li Lü; Jianqin Huang; Liangsheng Zhang; Zhengjia Wang (Food Chemistry, 2025)

Storm water management model simulations of the non-point source pollution load in the northern Anhui plain - Yun Wan; Mingjun Li; Nan Zhang; Mengwan Lin; Yuxuan Li; Peiqing Huang; Yuqi Feng; Bai Sun; Wei Wei; Shuguang Zhu (Ecohydrology & Hydrobiology, 2025)

An equitable spatial strategy for urban green space based on reconciling growing and shrinking neighbourhoods at the parcel level - Cheng Sun; Xiaoqing Song; Jianquan Cheng; Mingjun Peng; Xiangmei Li (Land Use Policy, 2025)

Nano polystyrene accelerated the reproductive toxicity induced by the Tris(1,3-dichloro-2-propyl) phosphate via Nhr-69-PISD-Drp-1-mediated mitochondrial fragmentation in Caenorhabditis elegans - Jia Wang; Yingchi Shi; Ke Meng; Mingjun Sun; Han Chen; Nan Jiang; Beijing Cheng; Mohan Hu; Ping Ye; Ran Liu (Environmental Pollution, 2025)

Reassessing the spatial and temporal evolution of the Southeast Asian Tin Belt: Insights into recurrent tin mineralization - Xiang Sun; Mingjun Zheng; Tong Pei; Pete Hollings; Xiaobo Si; Rongqing Zhang; Jun Deng (Earth-Science Reviews, 2025)

“Peeling egg” strategies for regenerating spent graphite with tailored surface/sub-surface and removed impurities towards high capacity - Tianjing Wu; Chen Liu; Mingjun Jing; Wei Sun; Yue Yang; Honghui Hu; Peng Ge (Chemical Engineering Journal, 2025)

Synchronous removal of heavy metals and ammonia-nitrogen by magnesium ammonium phosphate (MAP)-enhanced microbial induced calcite precipitation (MICP) - Lin Li; Huaji Sun; Chongyang Ren; Ziyi Zhao; Yueteng Song; Mingjun Wang; Shuiquan Chen; Gang Zhou (Journal of Hazardous Materials, 2025)

Double-confined FeCo nanoalloys as efficient and stable catalyst for selective hydrogenation of nitroarenes - Zhenyu Lei; Hao Sun; Lin Wu; Honglei Sun; Xiaomin Yang; Jingyao Liu; Peng Zhang; Mingjun Jia (Chemical Engineering Journal, 2025)

Toltrazuril inhibits Toxoplasma gondii by potentially targeting pyrimidine metabolism - An Yan; Kai He; Mingjun Xiong; Xu Wang; Wanxiao Jin; Ruibin Wu; Bolin Xia; Weiwei Sun; Baoliang Pan (Pesticide Biochemistry and Physiology, 2025)

Enhanced activation of PMS via Fe-MOFs-derives@BC for efficient removal of dyes: Complementary between radical and nonradical pathways - Mingjun Xie; Yuying Han; Na Wang; Zixuan Huang; Congting Sun (Journal of Water Process Engineering, 2025)

Positive Matrix Factorization (PMF) based on geochemical data for revising geological map in semi-desert covered terrains: A case study from a map sheer of Urat Rear Banner, Inner Mongolia, China - Yanling Sun; Xueqiu Wang; Hanliang Liu; Jian Zhou; Mingjun Xie (Geochemistry, 2025)

Thermodynamic and kinetic studies of CO2 hydrate stability in complex deep-oceanic environments - Lei Zhang; Ziming Yang; Yang Ge; Bingbing Chen; Huiru Sun; Yongchen Song; Mingjun Yang (Process Safety and Environmental Protection, 2025)

Study on the self-regeneration strategy of aged asphalt based on magnetic response controlled release microcapsules: A new sustainable self-regenerating pavement system - Yufeng Tian; Lei Xu; Daquan Sun; Hangtian Ni; Zhongbo Chen; Jianxiang Guo; Mingjun Hu (Journal of Cleaner Production, 2025)

Structure, synthesis and application of carbon based double single atom catalysts - Mingjun Xiao; Huizhen Sun (Desalination, 2025)

Water-in-eutectogel electrolytes for scalable solid-state electrochromic devices - Jianbo Deng; Mingjun Chen; Xiang Zhang; Hulin Zhang; Liping Hu; Shuokun Sun; Jiupeng Zhao; Yao Li (Chemical Engineering Journal, 2025)

In situ constructing artificial interfacial layer enables dendrite-free zinc anode in aqueous batteries - Canglong Li; Changding Wang; Jie Huang; Qiwen Zhao; Wen Liu; Yuxuan Song; Mingjun Rao; Fu Wan; Yuejiao Chen; Weigen Chen; Shuhui Sun (Chemical Engineering Journal, 2025)

Experimental research on the influence of wall effect on the structure of cumulated semi-cokes - Zhouzijing Yang; Peibin Zhang; Liying Zhang; Yuxiu Zhang; Xiangang Liu; Yuqiu Zhang; Haibo Gao; Yongqi Liu; Mingjun Sun; Yanxia Wang (Process Safety and Environmental Protection, 2025)

Potential function of plant-growth-promoting endophytic Serratia fonticola CPSE11 from Codonopsis pilosula in phytoremediation of Cadmium ion (Cd2+) - Mingjun Yang; Yunxing Fu; Shu Hu; Feifan Leng; Yan Zhuang; Wenbin Sun; Yonggang Wang (Journal of Environmental Management, 2025)

Monolithic and effective kinetic promoter formed by immobilizing MWCNTs on cellulose for efficient hydrate-based gas storage - Shuai Wang; Huilian Sun; Zhen Li; Changrui Shi; Lunxiang Zhang; Mingjun Yang; Yanghui Li; Cong Chen; Yongchen Song; Zheng Ling (Chemical Engineering Journal, 2025)

Correction to: Cassiterite geochronology and geochemistry of the Yunling Sn deposit: implication for late Cenozoic mineralization in western Yunnan, China - Ke Xiao; Xiang Sun; Rongqing Zhang; Mingjun Zheng; Tong Pei; Pete Hollings; Bin Fu; Jun Deng (Mineralium Deposita, 2025)

Insights and simulation models for long-distance water jet mining: Evolution of breaking depth and mass - Mingjun Jiang; Biao Sun; Yue Niu; Yingke Liu; Zhaoxi Long; Xiangyang Bu (Process Safety and Environmental Protection, 2025)

Male mites are the promising targets for control of Dermanyssus gallinae (Acari: Dermanyssidae) based on the reproductive biology research - Boxing Liu; Jiaqi He; Qi Liu; Bohan Wang; Mingjun Xiong; Weiwei Sun; Baoliang Pan (Veterinary Parasitology, 2025)

4-Nitrophenol at environmentally relevant concentrations mediates reproductive toxicity in Caenorhabditis elegans via metabolic disorders-induced estrogen signaling pathway - Jia Wang; Jiechen Yin; Danhong Peng; Xiaoqian Zhang; Zhouhong Shi; Weixi Li; Yingchi Shi; Mingjun Sun; Nan Jiang; Beijing Cheng; Xingchen Meng; Ran Liu (Journal of Environmental Sciences, 2025)

Cassiterite geochronology and geochemistry of the Yunling Sn deposit: implication for late Cenozoic mineralization in western Yunnan, China - Ke Xiao; Xiang Sun; Rongqing Zhang; Mingjun Zheng; Tong Pei; Pete Hollings; Bin Fu; Jun Deng (Mineralium Deposita, 2025)

Enhancement of power density and hydrogen productivity of the reverse electrodialysis process by optimizing the temperature gradient between the working solutions - Xi Wu; Youwen Zhang; Dexin Sun; Yibo Lv; Mingjun Liu; Xiaojing Zhu (Chemical Engineering Journal, 2024)

Effect of dietary vitamin D3 on growth performance and functional homeostasis of particular intestinal segments in grass carp fingerlings - Hao Sun; Pei Ge; Jiaxi Liu; Dan Xiong; Mingjun Zhu; Hong Zhou (Aquaculture International, 2024)

Biodegradation characteristics of p-Chloroaniline and the mechanism of co-metabolism with aniline by Pseudomonas sp. CA-1 - Mingjun Zhu; Yuhua Su; Yaru Wang; Yonglin Bo; Yufeng Sun; Qiyou Liu; Hang Zhang; Chaocheng Zhao; Yingying Gu (Bioresource Technology, 2024)

Degradation of petroleum hydrocarbon contaminants by Rhodococcus erythropolis KB1 synergistic with alfalfa (Medicago sativa L.) - Yan Nan; Ning Zhu; Shangchen Sun; Tianzhu Lei; Xiaopeng Guo; Feifan Leng; Mingjun Yang; Jixiang Chen; Yonggang Wang (Environmental Science and Pollution Research, 2024)

Analysis of the wet-towing operation of a semi-submersible floating wind turbine using a single tugboat - Mingsheng Chen; Yingjie Chen; Tingqiu Li; Yichang Tang; Jun Ye; Hao Zhou; Mingjun Ouyang; Xianxiong Zhang; Wei Shi; Xinghan Sun (Ocean Engineering, 2024)

Multiscale optimization on polymer-based rejuvenators for the efficient recycling of aged high-viscosity modified asphalt: Molecular dynamics simulation and experimental analysis - Mingjun Hu; Daquan Sun; Bernhard Hofko; Yiren Sun; Johannes Mirwald; Lei Xu (Journal of Cleaner Production, 2024)

Enhancing tetracycline degradation with biomass carbon quantum dot (CQDs)-modified magnetic heterojunction CeO2-Fe3O4 under visible light - Hua Chai; Ze Zhang; Jie Sun; Mingjun Zhong; Mengxue Liu; Jing Li; Zihao Chen; Beini Gong; Qiaoling Xu; Zhujian Huang; Lihua Cui (Journal of Environmental Chemical Engineering, 2024)

Performance evaluation of rhamnolipid biosurfactant produced by Pseudomonas aeruginosa and its effect on marine oil-spill remediation - Mingjun Zhu; Hang Zhang; Wu Cui; Yuhua Su; Shuo Sun; Chaocheng Zhao; Qiyou Liu (Archives of Microbiology, 2024)

Adsorption characteristics of Ag+ on sphalerite surface: a combined experimental and first-principle study - Heng Yu; Hongliang Zhang; Chenyang Zhang; Wei Sun; Mingjun Han; Rong Wang; Xin Wei; Songjiang Li (Environmental Science and Pollution Research, 2024)

Experimental and computational study on the adsorption mechanism of silver ions on galena surface - Heng Yu; Hongliang Zhang; Chenyang Zhang; Wei Sun; Mingjun Han; Rong Wang; Xin Wei; Songjiang Li (Journal of Water Process Engineering, 2024)

Characteristic microbiome and synergistic mechanism by engineering agent MAB-1 to evaluate oil-contaminated soil biodegradation in different layer soil - Yaru Wang; Shuo Sun; Qiyou Liu; Yuhua Su; Hang Zhang; Mingjun Zhu; Fang Tang; Yingying Gu; Chaocheng Zhao (Environmental Science and Pollution Research, 2024)

Enhanced atmospheric water cycle processes induced by climate warming over the three rivers source region - Zhilan Wang; Meiping Sun; Mingjun Zhang; Lei Zhang; Lailei Gu; Yu Zhang (Atmospheric Research, 2023)

Rapid Detection of blaKPC in Carbapenem-Resistant Enterobacterales Based on CRISPR/Cas13a - Mingjun Liang; Bin Xiao; Lidan Chen; Xiaoyan Huang; Jinchao Li; Zhenzhan Kuang; Xinping Chen; Xiuna Huang; Zhaohui Sun; Linhai Li (Current Microbiology, 2023)
Klebsiella pneumoniae carbapenemase (KPC) is a crucial enzyme that causes carbapenem resistance in Enterobacterales , and infections by these "superbugs" are extremely challenging to treat. Therefore, there is a pressing need for a rapid and accurate KPC detection test to control the prevalence of carbapenem-resistant Enterobacterales (CREs). In this study, we established a novel method for detection of bla KPC , the gene responsible for encoding KPC, based on a recombinase polymerase amplification (RPA) and a CRISPR/Cas13a reaction coupled to fluorophore activation (termed RPA-Cas13a assay). We carefully selected a pair of optimal amplification primers for bla KPC and achieved a lower limit of detection of approximately 2.5 copies/μL by repeatedly amplifying a recombinant plasmid containing bla KPC . The RPA-Cas13a assay demonstrated a sensitivity of 96.5% and specificity of 100% when tested on 57 bla KPC -positive CRE strains, which were confirmed by DNA sequencing. Moreover, in 311 sputum samples, the theoretical antibiotic resistance characteristics of bla KPC -positive strains obtained by the RPA-Cas13a assay were highly consistent with the results of antibiotic susceptibility test ( Kappa = 0.978 > 0.81, P < 0.01). In conclusion, the RPA-Cas13a system is a simple and one-hour efficient technology for the detection of a potentially fatal antibiotic resistance gene.

Increasing probability of record-population exposure to high temperature and related health-risks in China - Haiyan Zhang; Meiping Sun; Xiaojun Yao; Zhenyu Xie; Mingjun Zhang (Environmental Research, 2023)

Octyl gallate targeting the 3C-like protease exhibits highly efficient antiviral activity against swine enteric coronavirus PEDV - Mingjun Su; Baishuang Yin; Xiaoxu Xing; Zijian Li; Jiyu Zhang; Shufeng Feng; Lu Li; Feiyu Zhao; Xu Yang; Shiping Yu; Jun Wang; Yongchen Zhang; et al. (Veterinary Microbiology, 2023)

N-doped porous carbon-anchored zinc single-atom as an efficient and robust heterogeneous catalyst for glycerol carbonylation with urea - Jinghui Shi; Yunzuo Cui; Hao Sun; He Wang; Chunling Liu; Xiangxin Xue; Chuanbi Li; Longlong Geng; Jingyao Liu; Mingjun Jia (Chemical Engineering Journal, 2023)

Bimetallic MOF synergy molecularly imprinted ratiometric electrochemical sensor based on MXene decorated with polythionine for ultra-sensitive sensing of catechol - Zhiwei Lu; Kai Wei; Hao Ma; Rongtao Duan; Mengmeng Sun; Ping Zou; Jiajian Yin; Xianxiang Wang; Yanying Wang; Chun Wu; Gehong Su; Mingjun Wu; et al. (Analytica Chimica Acta, 2023)

N-nitrosamines-mediated downregulation of LncRNA-UCA1 induces carcinogenesis of esophageal squamous by regulating the alternative splicing of FGFR2 - Xianghu Wang; Mingjun Sun; Zhikui Gao; Lihong Yin; Yuepu Pu; Yong Zhu; Xiaobin Wang; Ran Liu (Science of The Total Environment, 2023)

Quantifying food loss along the animal products supply chain in China with large-scale field-survey based primary data - Ruigang Wang; Gang Liu; Lin Zhou; Zhenni Yang; Zhenchuang Tang; Shijun Lu; Mingjun Zhao; Huiwu Sun; Chuang Ma; Guangyan Cheng (Resources, Conservation and Recycling, 2023)

Thermoreversible aging in biorejuvenated asphalt binder - Jianmin Ma; Mingjun Hu; Tong Lu; Daquan Sun; Simon A.M. Hesp (Journal of Cleaner Production, 2023)

Comprehensive proteomic and phosphoproteomic reveal that Microcystin-LR contributed to the malignant progression of gastric cancer by estrogenic potency - Peiyan Yang; Peng Zhang; Yali Deng; Yinghao Liao; Xinxin Guo; Mingjun Sun; Lihong Yin; Ran Liu (Environmental Pollution, 2023)

Information entropy‐based projection of temperature variability under the warming trend in China - Meiping Sun; Haiyan Zhang; Xiaojun Yao; Mingjun Zhang; Qiaofeng Xing (International Journal of Climatology, 2022)
Quantifying the predictability of temperature in the future is a priority to inform policy and adaptation planning. Based on information entropy theory, this study uses global climate models within the Coupled Model Intercomparison Project Phase 6 (CMIP6) to project spatiotemporal changes and variability of temperature in China in the 21st century under different shared socio‐economic pathway scenarios (SSP2‐4.5 and SSP5‐8.5). Results show that the multimodel ensembled values can accurately capture the spatiotemporal pattern of temperature in China. The warming rates of annual mean temperature in China under SSP2‐4.5, SSP5‐8.5 scenarios are 0.42 and 0.61°C·decade −1 in the near‐term (2021–2050), 0.20 and 0.87°C·decade −1 in the long‐term (2071–2100), respectively. Warming is found to be the greatest in winter. Northeast, northwest, and the first region of southwest are anticipated to increase particularly rapidly, with larger increases than the rest of China. The intrayear variability of temperature (the variability of monthly mean temperature within the year or different seasons) in China shows obvious latitudinal differences. The variability of monthly mean temperature exhibits a decreasing trend in parts of northeast and the first region of southwest, and an increasing trend in northwest and parts of north. This is mainly resultant from the variability of monthly mean temperatures within spring and autumn. And this trend is more significant under the SSP5‐8.5 scenario than that under the SSP2‐4.5 scenario. The interannual variability of temperature (the variability of annual or seasonal mean temperature) in China shows significant regional difference, and two obvious regions with extreme variability (northeast and the first region of southwest). The trend of variability increases and then decreases under the SSP2‐4.5 scenario, whereas it keeps increasing under the SSP5‐8.5 scenario. This study helps to understand the spatiotemporal characteristics of temperature variability in China in the 21st century.

Optimized structural parameters and heat extraction capacity of a mixing device for constant pressure CO2 mineralization using alkaline waste - Wei Lu; Yang Yuan; Xiangming Hu; Guansheng Qi; Lulu Sun; Maoyuan Zhang; MingJun Wang; Min He (Environmental Science and Pollution Research, 2022)

Genetic variation and differentiation of Quercus variabilis populations at phosphate and non-phosphate rock sites in southwestern China - Huawei Ji; Baoming Du; Hongmei Du; Ningxiao Sun; Xu Yang; Mingjun Peng; Hongzhang Kang; Shan Yin; Chunjiang Liu (Plant Systematics and Evolution, 2021)

Arsenic exposure increased expression of HOTAIR and LincRNA-p21 in vivo and vitro - Jingwen Tan; Mingjun Sun; Quan Luo; Huiwen Sun; Mengjie Wang; Chenglan Jiang; Shuting Li; Yuefeng He (Environmental Science and Pollution Research, 2021)

Complete nucleotide sequence of a novel monopartite begomovirus infecting Ageratum conyzoides in China - Pengbai Li; Chenchen Jing; Rui Wang; Jiang Du; Gentu Wu; Mingjun Li; Xianchao Sun; Ling Qing (Archives of Virology, 2018)

Overexpression of VaWRKY14 increases drought tolerance in Arabidopsis by modulating the expression of stress-related genes - Langlang Zhang; Jun Cheng; Xiaoming Sun; Tingting Zhao; Mingjun Li; Qingfeng Wang; Shaohua Li; Haiping Xin (Plant Cell Reports, 2018)

First report of tobacco curly shoot virus infecting Malvastrum coromandelianum in China - Pengbai Li; Chenchen Jing; Ke Li; Jiang Du; Gentu Wu; Mingjun Li; Xianchao Sun; Ling Qing (Journal of Plant Pathology, 2018)

The Effect of Divalent Metal Ions and Recycle Ratio of UASB Reactor on the Formation of Anammox Granules and Its Treatment Performance - Jinxiang Fu; Mingjun Zhou; Jie Yun; Yang Su; Pengfei Yu; Ming Sun; Xinqi Ji (Water, Air, & Soil Pollution, 2017)

A Phytocystatin Gene from Malus prunifolia (Willd.) Borkh., MpCYS5, Confers Salt Stress Tolerance and Functions in Endoplasmic Reticulum Stress Response in Arabidopsis - Yanxiao Tan; Xiaoyu Wei; Ping Wang; Xun Sun; Mingjun Li; Fengwang Ma (Plant Molecular Biology Reporter, 2016)

The effect of different genome and cytoplasm on meiotic pairing in maize newly synthetic polyploids - Mingjun Cheng; Mingmin Zheng; Shipeng Yang; Yang Li; Xingchun Dong; Jing Li; Rulong Sun; Huaxiong Li; Shufeng Zhou; Yuanqi Wu; Tingzhao Rong; Qilin Tang (Euphytica, 2016)
Allopolyploidization plays the special role in the evolution of many crops. Moreover, the evolution in early stage of some allopolyploidization events is predicted to be effected by nuclear-cytoplasmic interactions. Maize and teosintes are well model system for study of genetic recombination in allopolyploidization. In order to investigate the effects of genome organization and cytoplasm on genome evolution in newly synthesized allopolyploids (neoallopolyploids), a series of neoallopolyploids were produced by reciprocal crosses of maize and Zea perennis . By using dual-color genomic in situ hybridization, intra- and intergenomic meiosis pairing of these polyploids were quantified and compared with regard to its genome organization and cytoplasm background. In the four neoallopolyploids, the stability of maize genome is consistently lower than that of Z. perennis genome. Additional, the stability of maize genome is affected by genome ploidy. The cytoplasm, genome composition and their interaction do have the special role in chromosome paring and the meiosis behaviors in Zea allopolyploids vary significantly and showed non-diploidization. Z. perennis cytoplasm may give a relatively relaxed environment for maize genome.

Hydrological processes of glacier and snow melting and runoff in the Urumqi River source region, eastern Tianshan Mountains, China - Meiping Sun; Xiaojun Yao; Zhongqin Li; Mingjun Zhang (Journal of Geographical Sciences, 2015)

Start of vegetation growing season on the Tibetan Plateau inferred from multiple methods based on GIMMS and SPOT NDVI data - Mingjun Ding; Lanhui Li; Yili Zhang; Xiaomin Sun; Linshan Liu; Jungang Gao; Zhaofeng Wang; Yingnian Li (Journal of Geographical Sciences, 2015)

Comparison of surface air temperature derived from NCEP/DOE R2, ERA-Interim, and observations in the arid northwestern China: a consideration of altitude errors - Shengjie Wang; Mingjun Zhang; Meiping Sun; Baolong Wang; Xiaoyan Huang; Qiong Wang; Fang Feng (Theoretical and Applied Climatology, 2015)

Increasing free-air 0°C isotherm height in Southwest China from 1960 to 2010 - Mingjun Zhang; Lei Dong; Shengjie Wang; Aifang Zhao; Fang Qiang; Meiping Sun; Qiong Wang (Journal of Geographical Sciences, 2014)

Changes in temperature extremes in the Yangtze River Basin, 1962–2011 - Qiong Wang; Mingjun Zhang; Shengjie Wang; Qian Ma; Meiping Sun (Journal of Geographical Sciences, 2014)

Functional characterization of the promoter region of human TNFAIP1 gene - Mingjun Liu; Zhenhua Sun; Aidong Zhou; Hong Li; Liping Yang; Chang Zhou; Rushi Liu; Xiang Hu; Jianlin Zhou; Shuanglin Xiang; Jian Zhang (Molecular Biology Reports, 2010)